Rail construction cost risk management with bow-tie analysis: Contractor’s perspective - Mohamad Zahierruden Ismail; Zuhaili Mohamad Ramly; Nur Fadilah Darmansah; Mohd Saidin Misnan (Emerald Publishing Limited, 2025)
Purpose – This study aims to examine the risks of cost overrun in rail construction from the contractor’s perspective. A three-phase approach is proposed (initial, planning and execution) to enhance comprehension of risk management optimization. Design/methodology/approach – Data collection involved distributing questionnaires to rail construction cost management professionals. The instrument was built by identifying key themes, concepts and findings from literature and pilot surveys. Data analysis consists of integrating the findings into a Probability Impact Matrix (PIM) and bow-tie diagrams based on probability and impact assessments. The diagrams created detailed risk mitigation tables and simplified response planning. Findings – Initial data analysis showed 36 factors causing cost overruns in 3 phases of rail construction. The responses were analysed by probability and impact, forming a risk matrix, which wasthen translated into a bowtie diagram. The information was then incorporated into the PIM that assists in determining appropriate risk responses based on risk levels. The index values ranged from moderate to very high. The execution phase exhibited the highest impact, particularly with risks associated with incompetent work schedule management and overdependence on specialist works, indicating a need for proactive risk mitigation strategies. Originality/value – This research indicates that the execution phase poses significant risks to rail cost performance, particularly in schedule and sub-contractor management. While contractors bear significant responsibility during this phase, government must be active in mitigating cost-related risks. Additionally, individual experience is crucial as contractors, clients and consultants are recommended to be adequately experienced to ensure a seamless process, minimal errors and effectively address multiple risks in the rail construction.